FEATURES OF INTESTINAL MICROBIOTA IN CHILDREN WITH A SYNDROME OF EXCESSIVE BACTERIAL GROWTH IN THE SMALL INTESTINE - L. A. Lityaeva; O. V. Kovalyova; O. G. Zhilenkova (Детские инфекции (Москва))
The purpose of the study was to determine the features of the parietal microbiota of the intestine in children with a verified syndrome of excessive bacterial growth in the small intestine. Clinical and laboratory examination of 25 children at risk of intrauterine infection at the age of 8 months — 4 years with a verified syndrome of excess bacterial growth in the small intestine was performed based on the results of the hydrogen breath test. Investigation of the species and quantitative composition of the parietal intestinal microbiota was carried out with the help of the gas chromatography-mass spectrometry method with determination of the concentration of microbial markers by drop of blood (laboratory of bifidobacteria of the Federal Budgetary Institute of Science Moscow Research Institute of Epidemiology and Microbiology name after G.N. Gabrichevsky). It was revealed that all of them recorded a high concentration of microbial markers of gram-negative anaerobic bacteria of the colon and viruses of the Herpes family due to a deficit of representatives of priority genera (Propionibacterium Freunderherii 5-fold, Eubacterium spp. 4.8-fold, Bifidobacterium spp. 4-fold, Lactobacillus spp. 1.5-fold) with an excess of endotoxin (by 1.5—2-fold) and a decrease in plasmalogen (by 2-fold). These data testify to the inflammatory process of the small intestinal mucosa, which aggravates the disturbances in its functioning and confirm the informative nature of the gas chromatography and spectrometry method.